Impediments to forgiveness Victim and transgressor attributions of intent and guilt. [article]. - Adams, Gabrielle S.
We investigate the possibility that victims and transgressors are predictably miscalibrated in their interpretation of a transgression, and that this has important implications for the process of forgiveness. Across 5 studies, we find that victims underestimate how much transgressors desire forgiveness. This is driven by a 2-part mediating mechanism: First, victims are more likely than transgressors to see the transgression as intentional, and second, this causes victims to believe transgressors feel less guilty than transgressors report feeling. Ultimately, this chain of asymmetries stymies the processes of forgiveness because victims tend to withhold forgiveness from those who actually desire it. The predicted effect emerged in the context of scenario studies (Studies 3 and 5), a real transgression that occurred in the lab (Study 4), transgressions from participants' pasts (Study 1), and transgressions from the same day (Study 2). In Study 4, we describe a new procedure in which 1 participant commits a real transgression against another participant, providing an effective means for researchers to study real-time transgressions from the perspective of both parties involved. Furthermore, in Study 5, we found that when victims were encouraged to empathize with the transgressor, the asymmetries were attenuated, suggesting a means of overcoming this impediment to forgiveness. -- (from the authors)